PENALARAN PROPORSIONAL SISWA SMP NEGERI 18 PONTIANAK DITINJAU DARI GAYA KOGNITIF SISTEMATIS DAN INTUITIF - Mella Widayanti; Yulis Jamiah; Romal Ijuddin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aimed to description the proportional reasoning abilities of middle school in solving comparison problem. Subject of this descriptive research were 4 student of VIII C class Middle School 18 Pontianak. The 4 student were 2 systematic cognitive style student and 2 intuitive cognitive style student. The instrument used to this reasech were written test and the cognitive-style inventory test. Data from the test were analyzed using steps data reduction, display data and conclusion. The result showed that the four student has different proportional reasoning abilities in solving comparison problem. The proportional reasoning abilities of subject S1 dan S2 tended to be at level 3 by using unit rate, factor of change and cross product algorithm strategy in solving direct propotion problem. The proportional reasoning abilities of subject S3 dan S2 tended to be at level 0 by using randomly uses numbers, operations, or strategies in solving inverse propotion problem. The proportional reasoning abilities of subject S3 dan S4 tended to be at level 0 by using randomly uses numbers, operations, or strategies in solving direct propotion and inverse propotion problem. Keywords: Intuitive Cognitive Style, Proportional Reasoning, Systematic Cognitive Style,